God’s Salvation in the Form of the Covenant - JIANG, Tian (Journal of Research for Christianity in China (JRCC), 2025)
God’s big plan for the world is revealed in the first book of the Bible, Genesis, and the heart of God’s mission is to bring salvation to humans in order to glorify his name in heaven and earth. The history recorded in Genesis is the history of God’s salvation, and God chose to fulfill the salvation in the form of a covenant. Our God is God of the covenant. God made the covenants with Adam, Noah, and Abraham in Genesis, as well as with Moses and David. All these covenants imply the typology of Christ. God’s promise and mission to the world in the beginning is finally accomplished in the covenant of Christ and will be completely fulfilled in his second coming.